2008
DOI: 10.1177/0013916508317222
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Confidence in Government and Information on Perceived and Actual Preparedness for Disasters

Abstract: This research examines perceived and actual preparedness for two types of natural hazard risks: earthquakes in the Los Angeles County area and hurricanes within the New Orleans metropolitan area. Using data collected from a sample of households in these regions, the influence of individuals' confidence in local government to manage a disaster and exposure to disaster preparedness information sources were tested as explanations for levels of perceived and actual preparedness. Regression analyses show that a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
198
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(225 citation statements)
references
References 35 publications
13
198
2
2
Order By: Relevance
“…on climate change or extreme weather events are underrepresented in some components and especially the component related to the need to prepare in advance for the possibility of extreme weather. This could be linked to the increased sense of preparedness that additional information sources provide, as found by previous studies (Basolo et al 2009). Many such events have the implicit intention of mobilizing for adaptation and preparedness to extreme weather events.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…on climate change or extreme weather events are underrepresented in some components and especially the component related to the need to prepare in advance for the possibility of extreme weather. This could be linked to the increased sense of preparedness that additional information sources provide, as found by previous studies (Basolo et al 2009). Many such events have the implicit intention of mobilizing for adaptation and preparedness to extreme weather events.…”
Section: Discussionsupporting
confidence: 54%
“…It could be the case that individuals, who feel more than average concerned, feel concerned because they lack more elaborate knowledge on extreme weather events. In a previous study, it was found that the number of information sources one is exposed to is positively linked to perceived level of preparedness (Basolo et al 2009). Individuals who participate thus in such events may feel more prepared, and thus less concerned, than individuals who do not participate in such events.…”
Section: Discussionmentioning
confidence: 95%
“…Previous research has established a positive relationship between the provision of disaster information and the adoption of hazard adjustments at the individual and organizational levels (Basolo et al 2009;Huss et al 2012;Perry and Nigg 1985;Sadiq and Weible 2010). We are 7 particularly interested in studies that examined this relationship at the organizational level.…”
Section: The Relationship Between Disaster Information and Hazard Adjmentioning
confidence: 97%
“…Previous studies have established a positive relationship between disaster information and the adoption of hazard adjustments at the individual and organizational levels (Basolo et al 2009;Huss et al 2012;Perry and Nigg 1985). This study builds on this literature by using social influence theory (Asch 1955;Deutsch and Gerard 1955) to explore whether FEMA is an influential provider of disaster information.…”
Section: Introductionmentioning
confidence: 95%
“…In general, studies argue that the effects of governmental information to people in situations of risk are not straightforward (e.g. Slovic, 2000;Schively, 2007;Basolo et al, 2009;Frewer, 2004). Slovic (2000), for example, argues that the extent to which the risk is perceived as involuntary is more important in understanding acceptance than the provided information alone.…”
Section: Governmental Information Provision About Highway Projectsmentioning
confidence: 99%